The University of Florence Technique for Robot-Assisted Kidney Transplantation: 3-Year Experience - Vignolini, Graziano; Greco, Isabella; Sessa, Francesco; Gemma, Luca; Pecoraro, Alessio; Barzaghi, Paolo; Grosso, Antonio; Corti, Francesco; Mormile, Nicola; Martiriggiano, Marco; Berni, Alessandro; Firenzuoli, Niccolò; et al. (Frontiers in Surgery, 2020)
Objective: To report the University of Florence technique for Robot-assisted Kidney Transplantation (RAKT) from living (LD) and deceased donors (DD), highlighting the evolution of surgical indications and technical nuances in light of a single surgeon’s learning curve. Materials and methods: A dedicated program for RAKT from LDs was developed at our Institution in 2017 and implemented with a specific framework for DDs. All RAKTs were performed by a single highly experienced surgeon. Data from patients undergoing RAKT between January 2017 and December 2019 were prospectively collected in a dedicated web-based data platform. In this report we provide a comprehensive step-by-step overview of our technique for RAKT, focusing on the potential differences in perioperative and mid-term functional outcomes between LDs vs DDs. Results: Overall, 160 KTs were performed in our center during the study period. Of these, 39 (24%) were performed with a robot-assisted laparoscopic technique, both from LDs (n=18/39 [46%]) and from DDs (n=21/39 [54%]). Eleven (11/39 [18%]), thirteen (13/39 [26%]) and fifteen (15/39 [30%]) RAKTs were performed in 2017,2018 and 2019, respectively, highlighting an increasing adoption of robotics for KT overtime at our Institution. Median time for arterial (19 min for LD and 18 min for DD groups), venous (21 min for LD, 20 min for DD) and uretero-vesical (18 min for LD and 15 for DD) anastomosis were comparable between the two groups (all p>0.05), as the median rewarming time (59 min vs 56 min, p=0.4). The rate of postoperative surgical complications according to Clavien-Dindo classification did not differ between the two study groups, except for Clavien-Dindo grade II complications (higher among patients undergoing RAKT from DDs, 76% vs 44%, p=0.042). Overall, 7/39 (18%) patients (all recipients from DDs) experienced DGF; two of them were on dialysis at last FU. Conclusions: Our experience confirms the feasibility, safety, and favorable mid-term outcomes of RAKT from both LDs and DDs in appropriately selected recipients, highlighting the opportunity to tailor the technique to specific recipient- and/or graft-characteristics. Further research is needed to refine the technique for RAKT and to evaluate the benefits and harms of robotics for kidney transplantation from DDs.